The Role Of Brand Trust As A Mediation Variable Of The Influence Of Brand Image And Social Media Marketing On Purchase Decisions For Sariayu Martha Tilaar Cosmetics In Dobo City, Aru Island District - Amin, Aswar; Asnawi, Aisah; Huwae, Victor Ernest (Jurnal Ekonomi, 2024)
This research aims to analyze the influence of brand image and social media marketing on purchasing decisions through brand trust as a mediating variable. The type of research used is quantitative research. The number of samples in this study was 116 respondents. The sampling technique uses a purposive sampling technique with a non-probability sampling method. Primary data in the research was obtained through distributing questionnaires to customers who use Sariayu Martha Tilaar Cosmetics in Dobo City, Aru Islands Regency. The data analysis method uses Partial Least Square (PLS) which can be operationalized via SmartPLS software. The results of the research show that brand image has a significant effect on brand trust, social media marketing has a significant effect on brand trust, brand trust has a significant effect on purchasing decisions, brand image has a significant effect on purchasing decisions through brand trust as a mediating variable, and social media marketing has a significant effect on purchasing decisions through brand trust as a mediating variable.